Why was Pitt not a mince pie?: Enjoying argument without end: creating confident historical readers at A-Level - Howells, Gary (Teaching history (London), 2011)
How can we help pupils learn to read historically? Gary Howells explores this question by explaining how he builds reading challenges into the course of his pupils' post-16 studies and by describing some of the tasks that pupils are set and the principles that underpin them. Howells argues that over time and through stepped and scaffolded tasks, we can gradually build pupils' confidence as historical readers. We can also support their enthusiasm and motivation to read closely, comparatively and critically.